Global corporate governance - John, Kose; Makhija, Anil K.; Ferris, Stephen P. (Advances in financial economics ;, 2017)
Advances in Financial Economics Volume 19 deals with International Corporate Governance, particularly the role played by boards of directors, internal organization design and governance mechanisms, franchise agreements, the effect of regulation and policy, the market for corporate control, and strategic alliances.- Resumé vydavatel